Análise do equilíbrio estático e de deformidades nos pés de crianças com paralisia cerebral - Costa, Thaís Delamuta Ayres da; Carvalho, Sebastião Marcos Ribeiro de [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (Universidade de São Paulo (USP), 2011)
The present study analyzed through baropodometry system, the feet’s types, the vision’s influence during static balance on orthostatic posture and the plantar pressure distribution in 16 children, aged from 6 to 15 years-old with diagnostic of cerebral palsy. We noted that the valgus foot was more common on the sample studied, diparetic spastic, hemiparetic spastic right, and hemiparetic spastic left and ataxic; the static balance on orthostatic posture with closed eyes was more instable compared to the orthostatic posture with opened eyes. In relation to the distribution of plantar pressure, we did not observe statistical significance and there was no correlation between age and the balance’s variables and the plantar pressure’s distribution. Therefore, we concluded that the vision is an important factor on postural control in children with cerebral palsy.

O presente estudo analisou, por meio de um sistema de baropodometria, os tipos de pé, a influência da visão no equilíbrio estático na postura ortostática e a distribuição da pressão plantar em 16 crianças, de 6 a 15 anos, com diagnóstico de paralisia cerebral. Os resultados indicaram que o pé valgo foi o mais comum dentre os tipos de paralisia cerebral estudadas, diparesia espástica, hemiparesia espástica direita, hemiparesia espástica esquerda e ataxia; o equilíbrio estático na postura ortostática de olhos vendados apresentou maior instabilidade do que quando com os olhos abertos; a distribuição de pressão plantar não apresentou significância estatística e não houve correlação significativa entre a idade e as variáveis de equilíbrio e de distribuição da pressão plantar. Desse modo, conclui-se que a visão é um fator importante no controle postural de crianças com paralisia cerebral.
Analysis of static balance and deformities on feet of children with cerebral palsy
Keywords: paralisia cerebral; fisioterapia; controle postural; criança; postura; deformidades do pé; child; cerebral palsy; posture; foot deformities